Genetic and environmental risk factors of acute infection-triggered encephalopathy - Mizuguchi, Masashi; Shibata, Akiko; Kasai, Mariko; Hoshino, Ai (Frontiers in Neuroscience, 2023)
Acute encephalopathy is a constellation of syndromes in which immune response, metabolism and neuronal excitation are affected in a variable fashion. Most of the syndromes are complex disorders, caused or aggravated by multiple, genetic and environmental risk factors. Environmental factors include pathogenic microorganisms of the antecedent infection such as influenza virus, human herpesvirus-6 and enterohemorrhagic Escherichia coli, and drugs such as non-steroidal anti-inflammatory drugs, valproate and theophylline. Genetic factors include mutations such as rare variants of the SCN1A and RANBP2 genes, and polymorphisms such as thermolabile CPT2 variants and HLA genotypes. By altering immune response, metabolism or neuronal excitation, these factors complicate the pathologic process. On the other hand, some of them could provide promising targets to prevent or treat acute encephalopathy.